Use of antimicrobial photodynamic therapy in the treatment of medication-related osteonecrosis of the jaw - da Silva, Nizyara Costa da Silva Costa; e Silva, Felipe Lima; Carlan, Leonardo Magalhães; de Farias Morais, Hannah Gil; Silva, Weslay Rodrigues; Silva de Arruda Morais, Maria de Lourdes (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Medication-related osteonecrosis of the jaw (MRONJ) is a debilitating complication associated with antiresorptive agents, in which treatment can be quite challenging. This study aimed to report two cases of cancer patients with MRONJ treated in a complementary manner by antimicrobial photodynamic therapy (aPDT). Both patients were male, 84 and 82 years old, respectively, and had a diagnosis of prostate adenocarcinoma and bone metastasis, treated with intravenous injections of bisphosphonates. The dental history for both was toothache, followed by extraction of dental elements that culminated with the appearance of necrotic bone in the mandibular region, which was confirmed with imaging exams and histopathological reports. The treatment protocol for both cases consisted of performing the aPDT once a week, associated with the use of 10 volumes hydrogen peroxide and 0.12% chlorhexidine digluconate for continuous use after oral brushing and amoxicillin with clavulanate three times a day for 7 days. The patient in case 1 performed 27 sessions, responded well to treatment, however, due to complications of the underlying neoplasm, he died without complete resolution of the osteonecrosis. In case 2, 32 sessions were carried out, with a good evolution of the symptoms. The patient is being followed up for 14 months, with no need for surgical intervention to date. Based on the reported cases and the literature survey, it can be concluded that aPDT can be an effective alternative in cases of MRONJ. The patients in the study in question showed success and control of the clinical picture.